Protozoários intestinais em amostras de fezes submetidas ao exame de rotina em laboratórios de análises clínicas: uma revisão sistemática - Garay, Júlia Caram (Universidade Federal de São Carlos, 2022)
Intestinal infections caused by protozoa contribute significantly to the burden of gastrointestinal diseases worldwide, but especially in less developed regions, where conditions associated with poor sanitation, water supply and hygienic habits favor the transmission of these parasites. Enteric protozoan species are associated with diarrheal diseases, often severe, especially in children and immunocompromised individuals. Even so, in routine, the diagnosis of intestinal protozoa has limitations, often underestimating the prevalence of infections in different populations. Thus, the present systematic review aims to synthesize and evaluate data available in the scientific literature on the prevalence of intestinal protozoa detected in stool samples submitted to routine examination in analysis laboratories, as well as on the parasitized population and the diagnostic methods used for the detection of these parasites. Searches were carried out in seven databases (EMBASE, PubMed, Science Direct, Scopus, Web of Science, LILACS and SciELO), without time and place restrictions, and language filters were used (Spanish, English and Portuguese). The articles obtained were reviewed and only those that met the inclusion and exclusion criteria were selected. The search in the databases resulted in the identification of 2754 publications, but only 20 met the selection criteria. All articles consisted of retrospective observational studies based on information about routine stool sample examinations performed in clinical laboratories located in Africa (Ethiopia, Ghana and Senegal), Middle East (Saudi Arabia and Iran), South America (French Guiana and Peru), Asia (India) and Europe (Italy). In total, 499.032 stool samples from individuals of both sexes and ages ranging from 11 days to 110 years were routinely examined. In 100% of the studies, microscopic examination was the technique of choice for the detection of intestinal parasites, with direct fresh examination being the most used laboratory method. Only two studies reported the use of molecular techniques and rapid immunochromatographic testing. The use of permanent staining techniques was reported in 80% of the studies. The prevalence of intestinal parasites detected in the selected studies ranged from 0,5 to 55,8%, and in 95% of the surveys infections caused by protozoa predominated and corresponded to 58 to 99% of the positive cases detected in the different laboratories. The prevalence of intestinal protozoa ranged from 0,5 to 46%. Pathogenic and non-pathogenic intestinal protozoan species were observed. Giardia duodenalis was the pathogenic species reported in 100% of the studies, followed by Entamoeba histolytica/dispar (85%) and Blastocystis spp. (60%). In addition to these, Cryptosporidium spp., Cyclospora cayetanensis, Cystoisospora belli and Dientamoeba fragilis were detected. Among the non-pathogenic species, Entamoeba coli was detected in most patients. In the present systematic review, the predominance and relatively high prevalence of intestinal protozoa reinforce the fact that the detection of these parasites in the human population is an important measure for the prevention and control of these infections, especially in less developed countries.
Intestinal protozoa in stool samples routinely examined in clinical analysis laboratories: a systematic review
Keywords: Diagnóstico Laboratorial; Protozoários Intestinais; Prevalência; Revisão Sistemática; Saúde Pública; Laboratory diagnosis; Intestinal protozoa; Prevalence; Systematic review; Public health; CIENCIAS BIOLOGICAS::PARASITOLOGIA